PERBUATAN PIDANA TERHADAP PENGEDARAN KOSMETIKA YANG TIDAK MEMILIKI IZIN EDAR DAN TIDAK MEMILIKI KEAHLIAN DALAM PRAKTIK KEFARMASIAN MENURUT UNDANG-UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN - Andi Nugraha; Dian Adriawan Dg Tawang (Jurnal Hukum Adigama, 2019)
Recent criminal offenses for the circulation of cosmetics without permission are increasingly worrying. Cosmetic products are imported products that are not registered by BPOM, so that cosmetic products are illegal products. Like the criminal act of cosmetics circulation without permission contained in the decision 334 / Pid.Sus / 2015 / PN.Dps. The main problem in this thesis is how the criminal acts against the perpetrators of the crime of cosmetics circulation that do not have marketing authorization and do not have expertise in pharmaceutical practices according to Law No. 36 of 2009 concerning Health. This study uses a type of normative juridical research that is analytically descriptive, using secondary data obtained by library studies and then analyzed qualitatively and uses deductive logic as a way of drawing conclusions. The results showed that the actions of the perpetrators charged in this case were Article 197 in conjunction with Article 106 paragraph (1) of Law No. 36 of 2009 concerning Health, but the judges should have applied Article 198 in conjunction with Article 98 paragraph (2) and (3) considering the perpetrators were not as a person who has the expertise to produce and distribute cosmetics. then the proven element is the element of article 198, namely everyone who does not have the expertise and authority to practice pharmacy as referred to in article 108.